2020
DOI: 10.1007/s42322-020-00059-2
|View full text |Cite|
|
Sign up to set email alerts
|

What future/s for outdoor and environmental education in a world that has contended with COVID-19?

Abstract: This is an unusual article in that it brings together the perspectives of many on this journal's editorial board, around the issue of contending with COVID-19. Twenty statements showcase a range of thoughts and experiences, highlighting the differences and similarities in the way the pandemic is impacting on the educational practice of outdoor and environmental education. The future is not yet written, of course, so it is worth thinking about how the current moment may impact on the months and years to come. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 21 publications
1
51
0
8
Order By: Relevance
“…Ayotte-Beaudet et al (2020) examined the impacts on outdoor program operations, Barton (2020) studied the changes in teaching strategies and techniques from the pandemic, and Mackenzie and Goodnow (2020) examined recreation user trends. In addition, Quay and his colleagues (2020) provided a more intimate and global perspective from 20 outdoor and experiential leaders and instructors on the impact of the virus on a broad variety of OAEE and environmental education programs across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…Ayotte-Beaudet et al (2020) examined the impacts on outdoor program operations, Barton (2020) studied the changes in teaching strategies and techniques from the pandemic, and Mackenzie and Goodnow (2020) examined recreation user trends. In addition, Quay and his colleagues (2020) provided a more intimate and global perspective from 20 outdoor and experiential leaders and instructors on the impact of the virus on a broad variety of OAEE and environmental education programs across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…The shortcomings of distance learningwhich include a lack of engagement in content learning, a lack of physical interaction with friends and a lack of immersion in the local environments (Azorín, 2020) -were even more prominent in the context of environmental education, in which the local outdoor environment plays a fundamental role. Research has found that students under lockdown conditions expressed their desire for the real learning that occurs during outdoor education (Quay et al, 2020). It is therefore important to explore environmental education in this situation.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…The pandemic sparked a global reaction that involved the influencing of policy makers, changing education systems and shifting environmental resource management practices (Quay et al, 2020). These different levels of change (the local, the national and the international) make the social-ecological system approach, and environmental education as part of it, well suited as a framework for this study.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations